Metabolic responses of date palm (Phoenix dactylifera L.) leaves to drought differ in summer and winter climate. (19th February 2021) - Du, Baoguo; Kruse, Joerg; Winkler, Jana Barbro; Alfarraj, Saleh; Albasher, Gadah; Schnitzler, Joerg-Peter; Ache, Peter; Hedrich, Rainer; Rennenberg, Heinz
Abstract: Drought negatively impacts growth and productivity of plants, particularly in arid and semi-arid regions. Although drought events can take place in summer and winter, differences in the impact of drought on physiological processes between seasons are largely unknown. The aim of this study was to elucidate metabolic strategies of date palms in response to drought in summer and winter season. To identify such differences, we exposed date palm seedlings to a drought-recovery regime, both in simulated summer and winter climate. Leaf hydration, carbon discrimination (Δ 13 C), and primary and secondary metabolite composition and contents were analyzed. Depending on season, drought differently affected physiological and biochemical traits of the leaves. In summer, drought induced significantly decreased leaf hydration, concentrations of ascorbate, most sugars, primary and secondary organic acids, as well as phenolic compounds, while thiol, amino acid, raffinose and individual fatty acid contents were increased compared with well-watered plants. In winter, drought had no effect on leaf hydration, ascorbate and fatty acids contents, but resulted in increased foliar thiol and amino acid levels as observed in summer. Compared with winter, foliar traits of plants exposed to drought in summer only partly recovered after re-watering. Memory effects on water relations, and primary and secondary metabolites seem to prepare foliar traits of date palms for repeated drought events in summer. Apparently, a well-orchestrated metabolic network, including the anti-oxidative system, compatible solutes accumulation and osmotic adjustment, and maintenance of cell-membrane stability strongly reduces the susceptibility of date palms to drought. These mechanisms of drought compensation may be more frequently required in summer.